IMPLEMENTASI MODEL COOPERATIVE LEARNING BERBANTUAN KOMPUTER DALAM PEMBELAJARAN PENDIDIKAN MATEMATIKA I PADA MAHASISWA PGSD UNNES - Trimurtini Trimurtini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
The lesson of Mathematics Education I in PGSD FIP UNNES still requires improvement. One of its way is by applying cooperative learning, that to train students to work along in group. The group efficacy will be reached if each group members succeed. Something else which need to be pay attention in this globalization is the using of computer as medium in learning activity. The problems are: (1)Is skill proceed in applying model cooperative learning with computer aid have an effect on to learning product of the PGSD students? ( 2)Is there any learning product mathematics of PGSD students differences between cooperative learning model with computer aid and conventional model? This is an experiment research, that compare cooperative learning model to conventional model in improving learning product of PGSD students in Mathematics Education I. The result and the conclusions are: (1)There are big influence (54,4%) of skill proceed in applying model cooperative learning with computer aid to learning product of PGSD students in Mathematics Education I, (2)The cooperative learning model with computer aid is more effective than conventional model in improving learning product of PGSD students in Mathematics Education I.